Some remarks on the Polish concepts of sources of international law in the interwar period - Mazurkiewicz, Maciej Jan (Studia Iuridica Toruniensia, 2017)
The questions relating to the sources of international law were often raised by eminent lawyers in the interwar period. A catalogue of sources, methods of legal norms’ reconstruction and a scope of their application were considered. After the adoption of the Statute of the Permanent Court of International Justice, these considerations were largely related to the provisions of Article 38, comprising the enumeration of legal sources. Among them were: international treaties, custom, general principles of law, judicial decisions, juristic writings and decisions ex aequo et bono. An important role of the aforesaid provisions of the Statute was pointed by their actual incorporation into the Statute of the current functioning International Court of Justice.